CONTRIBUCION PARA EL CONOCIMIENTO DE LA MORFOLOGIA DE LOS PLASMOCITOS HISTIOIDES - GONZALEZ GUZMAN, IGNACIO (Instituto Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1945)
Specimens were taken from the same subject simultaneously by (1) puncture and aspiration of the bone marrow, (2) direct collection by pressing and loosening of the bone marrow, and (3) section of the bony tissue The cytologic study will be reported later
BOL INST ESTUD MED BIOL
Keywords: CONTRIBUCION, CONOCIMIENTO, MORFOLOGIA, PLASMOCITOS, HISTIOIDES; CIENCIAS MEDICAS; BIOLOGIA CELULAR